A holistic perspective on hearing loss: first quality-of-life questionnaire (HL-QOL) for people with hearing loss based on the international classification of functioning, disability, and health - Illg, Angelika; Amann, Edda; Koinig, Karin A.; Anderson, Ilona; Lenarz, Thomas; Billinger-Finke, Mareike (Frontiers in Audiology and Otology, 2023)
Introduction To date, there is no quality-of-life questionnaire for people with hearing loss based on a multidisciplinary framework. Therefore, this study aimed to develop and validate a comprehensive assessment tool that addresses quality of life in people with hearing loss who use a cochlear implant based on the International Classification of Functioning, Disability, and Health (ICF). Methods In a first step, the Quality of Life in People with Hearing Loss Questionnaire (HL-QoL) was developed and tested for face validity. In a second step, the HL-QoL was evaluated and validated. In a third step, the HL-QoL was finalized based on the outcomes of the evaluation and validation. Results Eighty-four study participants fully completed the HL-QoL. The result of the test-retest reliability analysis was high and highly significant (n = 63; r = 0.914; p < 0.001). The mean total HL-QoL score (100.7 ± SD 24.58) suggests an overall high level of quality-of-life in this sample of people with hearing loss using a cochlear implant. The final version of the HL-QoL contains 21 items. Conclusion The HL-QoL has shown to be a valid and reliable tool to assess quality of life in people with hearing loss who use a cochlear implant. In addition to the total score, it is possible to calculate subscales based on the ICF components Body Functions and Activities and Participation.